Clinical signs and outcomes of beef cattle undergoing cesarean section because of dystocia - Hiew, Mark Wen Han; Baird, Aubrey N.; Constable, Peter D. (American Veterinary Medical Association, 2018)
OBJECTIVE: To characterize signalment, clinical signs, reproductive history, surgical management, and outcomes of beef cattle undergoing cesarean section because of dystocia at a veterinary teaching hospital. Design: Retrospective case series with nested cohort study. Animals: 173 beef cattle admitted to a veterinary teaching hospital from 2001 through 2010 that underwent cesarean section because of dystocia. Procedures: Medical records were reviewed and information collected on cattle signalment; reproductive history; cause of dystocia; anesthetic protocol; surgical management; number, sex, and body weight of calves delivered (alive or dead); perioperative treatment; duration of hospitalization; and discharge status. A questionnaire regarding postoperative fertility was mailed to all owners, and owners who did not respond were contacted via telephone. Results: Overall mortality rate for calves was high, with 37.6% (62/165) of calves delivered dead or dying ≤ 24 hours after cesarean section. Mortality rate was higher for female versus male calves and for calves from dams with signs of labor for ≥ 3 hours versus < 3 hours before hospital admission. Overall mortality rate for dams was low, with only 10 of 161 (6.2%) dams failing to survive for ≥ 21 days after hospital discharge. Postoperative fertility rate was acceptable, with 75% (44/59) of dams that were rebred after cesarean section giving birth to ≥ 1 live calf. Conclusions and Clinical Relevance: Cesarean section was a clinically useful method for resolving dystocia in beef cattle, providing a high dam survival rate and an acceptable postoperative fertility rate. Beef cattle producers should seek veterinary assistance whenever clinical signs of dystocia are noticed, preferably within 6 hours after onset of parturition.